Tracking of obesity among 2‐ to 9‐year‐olds in an electronic heath record database from 2006 to 2018 - David S. Freedman; Alyson B. Goodman; Raymond J. King; Heidi M. Blanck (Wiley, 2020)
Summary Background and Objective As obesity among children and adolescents is associated with major health risks, including the persistence of obesity into adulthood, there has been interest in targeting prevention efforts at children and adolescent. The longitudinal tracking of BMI and obesity, as well as the effects of initial age and duration of follow‐up on this tracking, were examined in a large electronic health record (EHR) database. Methods The data consisted of 2.04 million children who were examined from 2006 through 2018. These children were initially examined between ages 2 and 9 years and had a final examination, on average, 4 years later. Results Overall, children with obesity at one examination were 7.7 times more likely to have obesity at a subsequent examination than children with a BMI ≤ 95th percentile. Further, 71% of children with obesity at one examination continued to have obesity at re‐examination. Although 2‐year‐olds had a relative risk of 5.5 and a positive predictive value of 54%, then sensitivity of obesity at younger ages was low. Of the children who were re‐examined after age 10 y and found to have obesity, only 22% had a BMI ≥ 95th percentile at age 2 years. Conclusions Despite the tracking of obesity at all ages, these results agree with previous reports that have found that an elevated BMI at a very young age will identify only a small proportion of older children with obesity.